Syngress IT security project management handbook - Snedaker, Susan; Rogers, Russ. (Rockland, MA : Syngress, 2006)
The definitive work for IT professionals responsible for the management of the design, configuration, deployment, and maintenance of enterprise wide security projects. Provides specialized coverage of key project areas including Penetration Testing, Intrusion Detection and Prevention Systems, and Access Control Systems. The first and last word on managing IT security projects, this book provides the level of detail and content expertise required to competently handle highly complex security deployments. In most enterprises, be they corporate or governmental, these are generally the highest priority projects and the security of the entire business may depend on their success. * The first book devoted exclusively to managing IT security projects * Expert authors combine superb project management skills with in-depth coverage of highly complex security projects * By mastering the content in this book, managers will realise shorter schedules, fewer cost over runs, and successful deployments.
Identifying Objectives of IT Security Projects -- Taking Inventory of Cores Assets -- Identifying and Prioritizing Threats -- Existing Security Infrastructure -- Creating Penetrations Tests -- Analyzing Security Logs -- Creating Successful IDS -- Monitoring Host Servers -- Managing Internal Threats -- Contingency Planning and Disaster Recovery.
Includes index.
Keywords: Computer networks -- Security measures -- Handbooks, manuals, etc; Computer security -- Management -- Handbooks, manuals, etc; Electronic books; Handbooks, manuals, etc